Antidote to promoting a savings culture: Zimbabwe post dollarisation - Chikoko, Laurine (International Journal of Economics, Commerce and Management, 2016)
Zimbabwe adopted the multiple currency exchange rate system in 2009. There is general consensus on the benefits that accompanied the adoption of this exchange rate system, notably macroeconomic stability and improved financial intermediation. Deposits rose from US$1.3 billion in December 2009 to US$4.4 billion in January 2014 and further growing to US$5.1 billion by December 2014. Despite the upward trend, deposits have however remained short-term in nature signifying a low savings culture in Zimbabwe. The aim of this research is to provide insights on various strategies that can be adopted on part of the policy makers, industry developers and designers to promote a savings culture in Zimbabwe. These programs or strategies range from ones that literally compel households to save, to those that make it hard not to save. The study recommends that policy makers, industry developers and designers underscore the range of possibilities that exist to meet the needs of heterogeneous savers.